Результаты археологической разведки у с. Петровка - Кожухарь, В.К. (Материалы по археологии Северного Причерноморья, 2015)
In 2012, the employees of OAM NAN Ukraine examined the territory of the outskirts of the Petrovka village (Kominternovo district, Odessa region). Ceramics were collected from the surface of area 80u100 м extended in width direction 46°57'15,2''N 30°58'17,5''E. This site was earlier unknown. The author offers to name the new site “Petrovka-II” and to refer beforehand it to Sabatinovskaya culture (late bronze).